Empirical study on dividend policy of firms in East Asia. - Ho, Jinny Jie Ying. (2008)
Our study focuses on eight East Asian countries and we investigate the relationships between dividend payout and seven variables namely Expected Growth, Historical Revenue Growth, Firm Size, Leverage, Cash Flow Adequacy, Collateralizable Assets and Systematic Risk. Also, significant inter-industry and inter-country differences in dividend payout are found in our research.